Challenges of teaching skills (student teachers) in the kindergarten practical education process from their perspective (Raparin Journal of Humanities (RJH), 2024)
Practical education is a significant part of the educational and psychological tools represented by vision and practice. This has a positive impact on teacher preparation The second semester is devoted to practice in kindergartens, lasting six weeks. This is a real training opportunity for student teachers to demonstrate their skills and learn many teaching and kindergarten skills that will become a teaching experience in the future.The aim of this study is to identify the obstacles of student teacher teaching skills in the process of practical education in kindergartens in central Sulaimani, all of which were female. Utilizing a descriptive research method, the researcher employed a measurement tool consisting of 33 items categorized into six areas to identify obstacles to teaching skills among basic education students. The research sample comprised 82 student teachers. Statistical treatment of data was conducted using the SPSS program, facilitating the analysis of collected information and percentage weight. Finally, the researcher came to several conclusions:• Level of obstacles to teaching skills Practical education among teacher students is generally high.• The field of teaching materials, educational supervisors and kindergarten staff is generally at a weak level among student teachers, but the fields of planning, personality and teaching methods of teachers are at a high level.